Exploring consumers’ intention toward domestic energy-saving vehicles: Some insights from China - Wang, Zi-Xu; Jantan, Amer Hamzah Bin; Wu, Ruo-Xi; Gong, Yue; Cao, Meng-Ru; Wong, Philip Pong Weng; Wang, Lei (Frontiers in Psychology, 2022)
Policies to promote the usage of energy-saving vehicles (EVs) such as electric vehicles and hybrids were introduced and implemented in many countries due to increasing awareness of the potential benefits of such vehicles on environmental and energy conservation. However, despite consumers’ claims of their concerns and positive attitudes towards environmental issues, those claims have not been translated into energy-saving vehicles purchasing behaviour. Prior studies neglected the interrelationship between consumer ethnocentrism (CE), perceived value (PV) and consumer knowledge (CK) in influencing consumer behaviour, including pro-environmental behaviour. The current study examines the relationship between CE, PV, CK, perceived usefulness (PU), perceived ease of use (PEU), attitude and intention to purchase domestic energy-saving vehicles. A total of 396 completed questionnaires were collected through convenience sampling in Xuzhou, China. The survey data were subjected to descriptive analysis and analysis of variance using SPSS. In addition, confirmatory factor analysis and structural equation modelling were utilized for the hypotheses testing. The results revealed that CE positively influenced PV and CK; PV and CK positively influenced PU and PEU. CK positively influenced PV, while PU and PEU positively influenced attitude and intention, and PEU was shown to influence PU. Furthermore, attitude was shown to significantly influence intention to purchase domestic energy-saving vehicles. Lastly, the theoretical and practical implications of the outcomes were discussed, including limitations of the research.